The Effect of Engine Performance on The Speed of Purse Seine Vessels in Takalar Regency - Irawan Alham (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The waters of Takalar Regency are a good fishing area for pelagic fish species. Purse seine vessels are the type of fishing vessels that dominate the area. The purpose of the study was to examine the performance of engine work on the speed of purse seine ships in Takalar Regency. Data is grouped based on HP and ship speed then processed with shipping calculation formulas to obtain HP and ship speed. The result of the calculation of the amount of propulsion for purse seine ships in Takalar Regency with the largest CPI is 330 HP and for the lowest CPI is 115 HP. From the IHP value, a speed of 10.56 knots can be produced for the largest CPI and 2.50 knots for the lowest CPI